Optimizing Wood Pellet Production Through OEE and Supply Chain Engineering - Mohamad Fauzin Abdulloh; Johan Alfian Pradana; Rohmat Al Qusyairi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Efficient wood pellet production requires integrated management of machine performance and supply chain operations. PT Rafansa Sukses Sejahtera faces operational challenges, including machine downtime, inconsistent output, and defective products, caused by upstream issues such as delayed raw material supply, varying wood quality, and non-uniform particle size or moisture content. These factors disrupt lead times, reduce throughput, increase waste, and increase safety stock. This study analyzes machine performance using OEE, identifies production root causes through the 6M RCA, and evaluates supply chain indicators including lead time, throughput, waste, bottlenecks, and safety stock. Data were collected over six consecutive days using direct observation and expert judgment. Results showed OEE of 73.6–75.2%, downtime of 58–62 minutes, throughput of 845–855 kg/day, and waste of 5.54–5.59%. The RCA highlighted human, machine, material, method, measurement, and environmental factors as the main constraints. This study proposes an integrated OEE–RCA–supply chain framework to improve efficiency, reduce waste, and strengthen the resilience of the wood pellet supply chain.